Effect of foliar feeding of nano urea fertilisers on growth, yield and quality parameters on eggplant (Solanum melongena L.) - Nirmalya, Dhal; Alok, Nandi; Anup, Sahoo (Plant Science Today, 2026)
A field experiment was conducted on eggplant at the agricultural research station, Faculty of Agricultural Sciences, Siksha 'O' Anusandhan Deemed to be University (SOADU), Bhubaneswar, during winter season of 2023–2024 in order to assess the efficacy of nano fertilisers through foliar feeding and reduce the use of conventional fertilisers, which have significant adverse effects on the soil and the environment. It was laid out in the randomized block design (RBD) with 10 treatments and 3 replications. The treatments comprised of different concentrations of nano nitrogen and nano nitrogen, phosphorous and potassium (NPK). The treatment T10 (75 % recommended dose of nitrogen (RDN) + foliar spray of 1 % urea produced the highest yield (301.83 q ha-1) which was at par with T5 (75 % RDN + nano-urea foliar spray at 4 mL/L) and T3(100 % RDN as conventional fertiliser in soil). The highest total phenol was recorded in T5 (1.75 mg GAE/g) and the lowest (0.93 mg GAE/g) in T1(control). The highest glucose concentration of fruit was observed in T7 (7.38 %).